BUSINESS INNOVATION IN MICRO, SMALL, MEDIUM ENTERPRISES (MSMEs) (CASE STUDY ON PUTZA COFFEE SHOP) - Risnawati Risnawati; Selvi Fauzar; Ahmat Rahman; Andi Andi; Mohammad Farhan Mahyansah; Titik Jernih Hia (Universitas Kristen Indonesia Toraja, 2022)
(MSMEs) as a strategic force in accelerating regional development. In this connection, especially the micro business sector indeed occupies a strategic position in development as a safety belt, because the growth of MSMEs is increasing every year. Micro, Small and Medium Enterprises have an important position, not only in the absorption of labor and the welfare of the people in the regions, in many ways they become the glue and blocker of social problems. In this regard, efforts are needed to foster a conducive climate for the development of MSMEs in accelerating regional development. Placing micro, small and medium enterprises as the main target of development must be based on commitment and good coordination between the government, businessmen and non-business institutions and the local community by implementing an aggressive strategy based on economic networks (Partnerships); Developing micro, small and medium enterprises as a whole by how to provide positive and real support for the development of human resources (entrepreneurship training), technology, information, access to financing and marketing, Expansion of the export market, is an indicator of success in building a people-based business climate.